Estudo da degradação e potencial antigênico de proteínas do ovo no processamento de biscoitos semidoces e validação de método imunoenzimático - Pedro Paulo Borges dos Santos (2017)
The prevalence of food allergy is about 5 % in children and 3 % to 4 % in teenagers and adults. The food allergens can cause adverse effects even in small amounts. Among them, egg proteins are highlighted by high prevalence, being susceptible to changes in processing. Few existing methods for food allergen determination comply with the performance parameters required for validation. Therefore, the aims of this work was study the degradation of egg white proteins in semi-sweet biscuits, under different processing conditions, and validate an immunoenzymatic kit for this scope. Formulations containing 0,022 % of egg were baked in different times (5, 10, 15, 20, 25 and 30 minutes) and temperatures (150, 180 and 210 °C), in a factorial design, and were analyzed by the kit. In the single-laboratory validation, two different analytical batches of semi-sweet biscuits spiked with ovalbumin standard in nine concentration levels (0.125, 0.185, 0.25, 0.5, 1.0, 3.0, 4.5, 9 and 13.5 mg/kg) in 10 replicates, plus the blank, were analyzed. A significant reduction (p <0.05) in the egg protein content was observed in baked biscuits. With 25 minutes of baking, were evidenced reductions of 83.1; 92.6 and 100% for the temperatures 150, 180 and 210 ° C, respectively, indicating influence of the processing on the antigenic potential. The results of the quantitative approach of validation showed that the performance criteria were not complied. In the qualitative approach, 100 % of sensitivity and reliability rates were found for the blank samples. In the levels 0.125; 0.185 and 0.25 mg/kg the sensitivity and reliability rates were 0; 90 and 80 %, respectively. From the level 0.5 mg/kg, the estimated values of these rates were 100 %, demonstrating sensitivity of the method. The accordance ranged from 0.5 to 1.0 and concordance from 0.7 to 1.0. For the concentrations of 0; 0.125 and over 0.5 mg/kg the concordance reaches maximum values, showing standardization of the method. The detection limit was established as 0.2 mg/kg. The studied kit presented selectivity in the presence of the other allergenic protein beta-lactoglobulin. Thus, the baking conditions were evidenced as critical for the antigenicity of egg white proteins and the studied kit was considered appropriate for the detection of egg white proteins in semi-sweet biscuits, characterizing an important tool for the implementation of the control of food allergens labeling.